Applying Sharia in the West Facts, Fears and the Future of Islamic Rules on Family Relations in the West - Berger, Maria (Leiden University Press, 2013)
Shari'a, the framework of Islamic rules and norms, governs many aspects of human behavior. The contributors to Applying Shari'a in the West examine in depth how Muslims in the West shape their normative behavior on the basis of Shari'a and how Western societies and legal systems react thereto. With its explicit focus on social and family relations, these country and thematic studies provide a timely overview of the current state of Shari'a and outline aspects of possible future developments, studies, and policies.